Manajemen Konflik dan Pencegahan Kekerasan Berbasis Gender di Lingkungan Pesantren dan Sekolah Islam - Aanisah Agusnani Rizq; Achmad Zailani; Auni Luthfiah Nurfathina; Tin Amalia Fitri; Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study identifies Gender-Based Violence (GBV) within the environment of Islamic Boarding Schools (Pesantren) and Islamic Schools as a systemic managerial failure, exacerbated by unequal power relations and weaknesses in the existing management system. The critical gap lies in the institutions' dependence on informal conflict resolution mechanisms (internal resolution), which is problematic due to the lack of clear Standard Operating Procedures (SOPs), insufficient secure reporting channels (whistleblowing system), and a tendency to prioritize the institutional image over victim protection. Given the significant surge in GBV cases (e.g., 30 reported cases in the last three years), this research aims to formulate a robust and applicable Proactive Risk Management framework. The findings recommend a three-dimensional conflict management mechanism: the Preventive Dimension (through curriculum integration and codes of ethics), the Responsive Dimension (through the establishment of an independent Sexual Violence Prevention and Handling Task Force (Satgas PPKS), transparent SOPs, and firm sanctions), and the Protection Dimension (through psychosocial services and restitution for victims). The implementation of this framework is highly urgent to transform Islamic Education Management (MPI) and realize a safe, inclusive, and violence-free learning environment.